Current practice in assessment and management of malnutrition in surgical oncology practice - An ESSO-EYSAC snapshot analysis - Brandl, Andreas; Lundon, Dara; Lorenzon, Laura; Schrage, Yvonne; Caballero, Carmela; Holmberg, Carl Jacob; Santrac, Nada; Smith, Henry; Vasileva-Slaveva, Mariela; Montagna, Giacomo; Bonci, Eduard-Alexandru; Sgarbura, Olivia; et al. (European journal of surgical oncology, 2024)
INTRODUCTION: Malnutrition is common in patients suffering from malignant diseases and has a major impact on patient outcomes. Prevention and early detection are crucial for effective treatment. This study aimed to investigate current international practice in the assessment and management of malnutrition in surgical oncology departments. MATERIAL AND METHODS: The survey was designed by European Society of Surgical Oncology (ESSO) and ESSO Young Surgeons and Alumni Club (EYSAC) Research Academy as an online questionnaire with 41 questions addressing three main areas: participant demographics, malnutrition assessment, and perioperative nutritional standards. The survey was distributed from October to November 2021 via emails, social media and the ESSO website to surgical networks focussing on surgical oncologists. Results were collected and analysed by an independent team. RESULTS: A total of 156 participants from 39 different countries answered the survey, reflecting a response rate of 1.4%. Surgeons reported treating a mean of 22.4 patients per month. 38% of all patients treated in surgical oncology departments were routinely screened for malnutrition. 52% of patients were perceived as being at risk for malnutrition. The most used screening tool was the "Malnutrition Universal Screening Tool" (MUST). 68% of participants agreed that the surgeon is responsible for assessing preoperative nutritional status. 49% of patients were routinely seen by dieticians. In cases of severe malnutrition, 56% considered postponing the operation. CONCLUSIONS: The reported rate of malnutrition screening by surgical oncologists is lower than expected (38%). This indicates a need for improved awareness of malnutrition in surgical oncology, and nutritional screening.
Keywords: chirurgická onkologie; Neoplasms; Surgical oncology; průzkumy a dotazníky; podvýživa; hodnocení stavu výživy; Malnutrition; Humans; Nutrition Assessment; Screening; Practice Patterns, Physicians'; Pre-habilitation; nádory; Surveys and Questionnaires; lékařská praxe - způsoby provádění; Surgical Oncology; lidé; Cancer